The Freedom of Labor as a Socio-Philosophical Factor and its Role in Human Development - Oybek, Karimov (International Journal of Formal Education, 2025)
This article examines labor freedom as a socio-philosophical factor, focusing on its role in realizing human potential, ensuring social justice, and promoting sustainable development. The philosophical and legal aspects of labor as a manifestation of human nature and a driver of social change are analyzed. The paper also discusses the consequences of the absence of labor freedom, such as forced labor, gender inequality, and child labor. The research draws upon classical and contemporary philosophical thought, statistical data, and both Uzbek and international experiences to derive socio-philosophical conclusions.